Publisher Correction: Effect of Ribs Configurations on Heat Transfer Enhancement for W-Shaped Ribs in a Square Duct (Arabian Journal for Science and Engineering, (2023), 10.1007/s13369-023-07662-7) - Gajghate, Sameer Sheshrao; Deshpande, Onkar Prakash; Desai, Amit Uttam; Deshmukh, Akshay Dilip; Kharade, Shrikant Uttam; Pal, Sagnik; Cardoso, Elaine Maria [UNESP]; Saha, Bidyut Baran; Bhaumik, Swapan (Springer Nature, 2023)
In the original publication, the affiliation cross-reference for author Dr. Swapan Bhaumik4 was wrong. It should be Swapan Bhaumik3. This has been corrected in the original article.
Publisher Correction: Effect of Ribs Configurations on Heat Transfer Enhancement for W-Shaped Ribs in a Square Duct (Arabian Journal for Science and Engineering, (2023), 10.1007/s13369-023-07662-7)